A comparative study of the functional properties of acid modified cassava and waxy maize starch - Mooney, Caroline Banzon
This study was undertaken primarily to determine if it was possible to substitute acid modified cassava starch for acid modified waxy maize starch. In the first phase, the gelatinization characteristics of native cassava starch were determined. Its behavior under different simulated conditions of acidity, shearing rates and temperature was also determined by measuring changes in its viscosity. The storage stability of the starch under low temperature was also studied. On the second phase, the acid modified cassava starch was produced based on the procedure obtained from the Department of Science and Technology. The gelatinization characteristics and the behavior of the produced starch under different simulated processing conditions of acidity, shearing rates and temperature were compared to a commercially available waxy maize starch. In the third phase, the utilization of the modified starches in gum candies was tested. In the first phase, the native cassava starch paste was found to be unstable towards acid except at a pH of 4.0. The starch paste was found to be unstable towards different shearing rates and high temperature. It was, however, found to be stable for two weeks under low temperature since no syneresis of the starch paste occurred. In the second phase, the two modified starches produced transparent pastes. In terms of texture, the acid modified waxy maize starch was thicker than the acid modified cassava starch. The behavior of the two modified starches was found to be exactly the opposite of each other at different conditions of acidity, shear and high temperature. At low temperature conditions, the behavior of both starches were found to be comparable. Both of them exuded water to the same extent except on the second day. In the third phase, a panel subjectively analyzed the texture of the gum candies incorporated with the modified starches. The candies were found to be significantly different from each other by a moderate to a large degree. Based on the results of the three phases of this study, it was concluded that the acid modified cassava starch has functional properties entirely different from that of acid modified waxy maize starch except at low temperature conditions.